Corporate venture capital portfolios and firm innovation - Wadhwa, Anu; Phelps, Corey; Kotha, Suresh (Journal of Business Venturing, 2016)
This study examines the conditions under which portfolios of corporate venture capital (CVC) relationships influence corporate investor innovation performance. We investigate this question using longitudinal data on CVC investment portfolios of 40 telecommunications equipment manufacturers. We find an inverted U-shaped effect of portfolio diversity on corporate investor innovation performance. We also find that the effect of diversity depends on the depth of knowledge resources available in the portfolio. These results contribute to the interorganizational learning, corporate venture capital and open innovation literatures by showing how the breadth and depth of knowledge resources available in a portfolio of external partnerships with young ventures interact to influence firm innovation.